Reason and imagination : (World Scientific, 1996)
This book is about the recognition of new organic chemistry. It is also about the discovery and invention of chemical reactions. In addition, it deals with the determination of structure by chemical degradation during the epoch when physical methodswere not well developed. Also presented are new reagents and new types of functional groups never seen in chemistry before